Diagnostic accuracy of cervical cancer screening strategies for high-grade cervical intraepithelial neoplasia (CIN2+/CIN3+) among women living with HIV: A systematic review and meta-analysis. (November 2022) - Kelly, Helen; Jaafar, Iman; Chung, Michael; Michelow, Pamela; Greene, Sharon; Strickler, Howard; Xie, Xianhong; Schiffman, Mark; Broutet, Nathalie; Mayaud, Philippe; Dalal, Shona; Arbyn, Marc; et al.
Summary: Background: We systematically reviewed the diagnostic accuracy of cervical cancer screening and triage strategies in women living with HIV (WLHIV). Methods: Cochrane Library, Embase, Global Health and Medline were searched for randomised controlled trials, prospective or cross-sectional studies published from database inception to 15 July 2022 reporting diagnostic accuracy of tests in cervical cancer screening and triage of screen-positive WLHIV. Studies were included if they reported the diagnostic accuracy of any cervical cancer screening or triage strategies for the detection of histologically-confirmed high-grade cervical intraepithelial neoplasia (CIN2+/CIN3+) among WLHIV. Summary data were extracted from published reports. Authors were contacted for missing data where applicable. Sensitivity and specificity estimates for CIN2/3+ were pooled using models for meta-analysis of diagnostic accuracy data. Study quality was assessed using the QUADAS-2 tool for the quality assessment of diagnostic accuracy studies. PROSPERO registration:CRD42020189031. Findings: In 38 studies among 18, 737 WLHIV, the majority (n=19) were conducted in sub-Saharan Africa. The pooled prevalence was 12.0% (95%CI:9.8-14.1) for CIN2+ and 6.7% (95%CI:5.0-8.4) for CIN3+. The proportion of screen-positive ranged from 3-31% (visual inspection using acetic acid[VIA]); 2-46% (high-grade squamous intraepithelial lesions, and greater [HSIL+] cytology); 20-64% (high-risk[HR]-HPV DNA). In 14 studies, sensitivity and specificity of VIA were variable limiting the reliability of pooled estimates. In 5 studies where majority had histology-confirmed CIN2+, pooled sensitivity was 56.0% (95%CI:45.4-66.1; I 2 =65% ) for CIN2+ and 65.0% (95%CI:52.9-75.4; I 2 =42%) for CIN3+; specificity for <CIN2 was 73.8% (95%CI:59.8-84.2, I 2 =94% ). Cytology was similarly variable (sensitivity of ASCUS+ for CIN2+ range: 58-100%; specificity: 9-96%). In 28 studies, sensitivity of tests targeting 14-HR-HPV types was high (91.6%, 95%CI:88.1-94.1; I 2 =45% for CIN2+ and 92.5%, 95%CI:88.4-95.2; I 2 =32% ) for CIN3+); but specificity for <CIN2 was low (62.2% (95%CI:57.9-66.4; I 2 =92% ). Restriction to 8-HR-HPV increased specificity (65.8%; Relative specificity[RSpec] vs. 14-HR-HPV=1.17; 95%CI:1.10-1.24) with no significant change in sensitivity (CIN2+:85.5%; Relative Sensitivity[RSens]=0.94, 95%CI: 0.89-1.00; CIN3+:90%; RSens=0.96, 95%CI:0.89-1.03). VIA triage of 14-HR-HPV positive women decreased sensitivity for CIN2+ compared to HPV-DNA test alone (64.4% vs. 91.6%; RSens=0.68, 95%CI:0.62-0.75). Interpretation: HPV-DNA based approaches consistently showed superior sensitivity for CIN2+/CIN3+ compared to VIA or cytology. The low specificity of HPV-DNA based methods targeting up to 14-HR-HPV could be improved significantly by restricting to 8-HR-HPV with only minor losses in sensitivity, limiting requirement for triage for which optimal approaches are less clear. Funding: World Health Organisation; National Cancer Institute; European Union's Horizon 2020 and Marie Skłodowska-Curie Actions programme.